The Intra-Dependence of Viruses and the Holobiont - Grasis, Juris A. (Frontiers in Immunology, 2017)
Animals live in symbiosis with the microorganisms surrounding them. This symbiosis is necessary for animal health, as a symbiotic breakdown can lead to a disease state. The functional symbiosis between the host, and associated prokaryotes, eukaryotes, and viruses in the context of an environment is the holobiont. Deciphering these holobiont associations has proven to be both difficult and controversial. In particular, holobiont association with viruses has been of debate even though these interactions have been occurring since cellular life began. The controversy stems from the idea that all viruses are parasitic, yet their associations can also be beneficial. To determine viral involvement within the holobiont, it is necessary to identify and elucidate the function of viral populations in symbiosis with the host. Viral metagenome analyses identify the communities of eukaryotic and prokaryotic viruses that functionally associate within a holobiont. Similarly, analyses of the host in response to viral presence determines how these interactions are maintained. Combined analyses reveal how viruses interact within the holobiont and how viral symbiotic cooperation occurs. To understand how the holobiont serves as a functional unit, one must consider viruses as an integral part of disease, development, and evolution.